(untitled) (Contemporary Journal of Social Science Review, 2024)
This study aimed to develop a valid and reliable measurement scale for assessing stigma and discrimination related to mental health among young adults in the specific context of Pakistan. The Mental Health Stigma Scale was developed through four stages, beginning with domain identification and item pooling, followed by expert content validation, pilot testing, and exploratory factor analysis. Data were collected from 300 young adults (150 male and 150 women) aged between 18 to 30 years (M Age = 20.76, S.D = 2.15) using a convenient sampling method. Strong internal consistency, reliability was indicated by the 11-item Mental Health Stigma and Discrimination Scale’s Cronbach’s alpha coefficient of 0.702. The validity of the scale was established by exploratory factor analysis. Mental Health stigma and Discrimination scale is first scale, developed in Pakistan, that evaluates stigma and discrimination related to mental health. The scale consists of 11 items, with two culturally relevant sub-scales, i.e., “Mental Heath Stigma and Discrimination” and “Stigma and Supernatural Attributions”. The scale will prove to be a valuable tool in assessing the impact of stigma on individuals’ mental well-being and in facilitating the development of tailored treatment plans that address the specific challenges associated with stigma in Pakistan.